2022
DOI: 10.1186/s40659-022-00401-6
|View full text |Cite|
|
Sign up to set email alerts
|

Utility of melatonin in mitigating ionizing radiation-induced testis injury through synergistic interdependence of its biological properties

Abstract: Background Ionizing radiations (IR) have widespread useful applications in our daily life; however, they have unfavorable effects on reproductive health. Maintaining testicular health following IR exposure is an important requirement for reproductive potential. The current study explored the role of melatonin (MLT) in mitigating IR-induced injury in young adult rat testis. Methods Rats were given daily MLT (25 mg/kg) for 3 and 14 days after receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…Particularly, spermatogonia was most damaged by diquat in an apoptotic manner in vivo and in vitro. In contrast, melatonin treatment reduced TUNEL-positive cells, which agrees with the report that melatonin can protect the testes from external harm via a synergistic interaction of its antioxidant, anti-inflammatory, and anti-apoptotic properties [ 17 ]. This was also confirmed by changes in Cleaved-Caspase3 and Bax/Bcl2 levels induced by melatonin treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Particularly, spermatogonia was most damaged by diquat in an apoptotic manner in vivo and in vitro. In contrast, melatonin treatment reduced TUNEL-positive cells, which agrees with the report that melatonin can protect the testes from external harm via a synergistic interaction of its antioxidant, anti-inflammatory, and anti-apoptotic properties [ 17 ]. This was also confirmed by changes in Cleaved-Caspase3 and Bax/Bcl2 levels induced by melatonin treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Melatonin modulates testicular functions by regulating testosterone production in Leydig cells [ 12 ], proliferation, and energy metabolism in Sertoli cells [ 13 ], and consequently influences spermatogenesis [ 14 ]. Specifically, melatonin and its metabolites are potent free-radical scavengers that protect the testes against oxidative damage caused by hyperthermia [ 15 ], irradiation [ 16 , 17 ], and environmental toxins [ 18 , 19 ]. However, whether melatonin can alleviate oxidative stress and testicular damage induced by diquat remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of previous studies led us to hypothesize that MLT might serve as a promising preventative agent that could ameliorate radiation-induced injury. 22,23 To verify this hypothesis, we assessed the regulatory effects of MLT on irradiated HFD-fed mice.…”
Section: Food and Function Papermentioning
confidence: 99%
“…20,21 Moreover, MLT has also been shown to alleviate ionizing radiation (IR)-induced damage, including intestinal damage and testis injury. 22,23 Furthermore, MLT supplementation can effectively regulate obesity; 24 however, little is known about the effect of MLT on radiation-induced damage in HFD-fed mice.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in Figs. 3D and 4.…”
mentioning
confidence: 99%